Overview of Daily Living Activities in Patients with Osteoarthritis - Afra Qhotrunnada Syifa; Mohammad Arifin Noor; Suyanto Suyanto (Lembaga Pengembangan Kinerja Dosen, 2026)
Osteoarthritis is a degenerative joint disease that causes cartilage damage, pain, stiffness, and decreased joint function, which can impair patients’ ability to perform Activities of Daily Living (ADL). Limitations in ADL reduce independence and quality of life, particularly among elderly patients. This study aimed to describe the level of ADL independence in patients with osteoarthritis at Sultan Agung Islamic Hospital, Semarang. A categorical descriptive study with a cross-sectional approach was conducted involving 98 respondents selected through stratified random sampling. Data were collected using a modified Barthel Index and analyzed descriptively to determine the distribution of dependency levels. The findings showed that most patients experienced mild dependency, followed by moderate dependency, while only a small proportion were fully independent. The activities most frequently affected were mobility, walking, and stair climbing. These results indicate that osteoarthritis significantly affects functional ability in daily activities. The findings are expected to provide evidence-based information for nursing practice, particularly in planning rehabilitative and supportive interventions aimed at improving functional independence and quality of life in patients with osteoarthritis.